Kinerja Finansial Usaha Distribusi Sayur (Studi Kasus: Wijaya Vegetables di Kecamatan Baturiti Kabupaten Tabanan Provinsi Bali) - I PUTU YUDHI ARTA WIJAYAKUSUMA; I MADE ANTARA; NI WAYAN SRI SUTARI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2022)
Financial Performance Of Vegetable Distribution Business (Case Study: Wijaya Vegetables In Baturiti District, Tabanan Regency, Bali Province). One of the current problems in the agricultural sector is unjust trade caused by long supply chains. Wijaya Vegetables has succeeded in innovating to shorten the market chain so that its business model and financial analysis are important to be understood. Wijaya Vegetables is a sociopreneurship that distributes fresh vegetables directly from farmers in Baturiti District, Tabanan Regency, Bali Province. Financially, Wijaya Vegetables has a relatively increased profit. Asset composition which is dominated by current assets shows good business activity. The R/C ratio value of 1.28 indicates that the business is financially viable, and the average monthly profit margin of 40% indicates that the business has healthy growth. The allocation of profits used for social aspects should be reconsidered considering the amount is quite large. Utilization of debt should also be maximized. Further research that discusses the social aspects and business model of Wijaya Vegetables is important to do.